Improving a quality system through a management process at Trane Thailand. (20th December 2010) - Phusavat, Kongkiti; Chuancharoen, Supakij; Nitipavachon, Suvit; Kanchana, Rapee; , Binshan Lin
The study deals with the improvement of a management process for Trane Thailand. A management process consists of performance measurement, analysis and improvement. The focus on this improvement deals with customer satisfaction information. It is part of the company's efforts to apply Thailand Quality Award. The methodology involves with the focus-group discussions and the applications of correlation analysis on customer satisfaction and its desirable impacts. The findings show that higher satisfaction on telephone and communication accessibility would lead to higher sale revenues from spares and parts within one quarter. There are three other interrelationships resulted from customer satisfaction. The implications from this study are customer satisfaction needs to be related to financial performance of an organisation for better understanding and information analysis. Finally, improving a management process is one of the key tasks in ensuring long-term organisational competitiveness and to prepare for the future award application.